Analysis of functioning environmental of oil and gas enterprises based on econometric support - Побігун, С. А. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
The paper investigates the existing approaches to understanding the analysis and evaluation of the impact of individual components functioning business environment. The analysis of recent studies led to the conclusion about the need to study not only strategic decisions based on strategic analysis of all components of both the internal and external environment, but also on the basis of their predictability and trends change. Determined that the vast majority of the construction strategy and future trends of the company is based on expert judgments or scorecards that do not fully reflect the impact on the strategic enterprise performance. However, to improve the quality of the analysis the application of methods and tools of econometrics as a system of econometric support in all phases of strategic analysis. This approach allows to evaluate not only the impact but also predictability and trends change individual components functioning business environment. Given the significant impact of oil and gas companies on the environment indicated that it is appropriate to assess the environment of such enterprises in sustainable development criteria.